Quad Bikes - a continuing issue in Aotearoa New Zealand - Crawford, Joanne (New Zealand Journal of Health and Safety Practice, 2025)
Quad bike accidents remain a cause for concern with 697 serious harm incidents and 79 fatalities reported from 2006 to 2023. This rapid review aimed to collate research on injury mechanisms, environmental factors and harm reduction initiatives. A total of 32 papers were included in the review and identified that there are some common factors involved in accidents including rollover events, the presence of a slope, males are more likely to have an accident and younger and older riders are more at risk. In terms of prevention, rollover protection devices have shown a reduction in fatalities where the use of such devices is supported by both enforcement activity and education. While legislation is difficult to enforce, standards have been found to be successful in reducing fatalities in Australia. Training courses have been found to increase the self-report of the intention to change behaviours including wearing helmets. This has not been evaluated through actual behaviour change. There is still limited information around other intervention strategies including attitude and risk perception but understanding these factors is essential in any plan for change. The review proposes not just workplace hierarchy of controls but also societal level interventions.